2014
DOI: 10.1186/1752-1947-8-220
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-induced cardiomyopathy: a case report and review of the literature

Abstract: IntroductionNewly developed antineoplastic drugs have resulted in improvements in morbidity and mortality from many forms of cancers. However, some of these new chemotherapeutic agents have potentially lethal side effects, which are now being exposed with their widespread use. Gemcitabine is a nucleoside analog, which is a commonly used agent for various solid organ malignancies. Phase 1 and 2 trials with gemcitabine did not show significant risk for cardiotoxicity; however, with its widespread clinical use ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…In these trials, patients who developed cardiomyopathies had underlying coronary artery disease, whereas our patient had no history of coronary disease. Outside of clinical trials, gemcitabine‐induced cardiomyopathy has been reported only once in the literature 2. The patient described was similar to ours.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In these trials, patients who developed cardiomyopathies had underlying coronary artery disease, whereas our patient had no history of coronary disease. Outside of clinical trials, gemcitabine‐induced cardiomyopathy has been reported only once in the literature 2. The patient described was similar to ours.…”
Section: Discussionsupporting
confidence: 82%
“…Outside of clinical trials, gemcitabine-induced cardiomyopathy has been reported only once in the literature. 2 The patient described was similar to ours. He did not have prior coronary artery disease or risk factors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our previous study showed that benzothiazole compounds dose-dependently inhibit the proliferation of C6 (rat brain tumor) and HeLa (human uterine cancer) cell lines (25). Gemcitabine is generally used in therapy of pancreatic, bladder, breast, ovarian and non-small cell lung (26)(27)(28)(29)(30) cancer. Both compounds 4a and 4b demonstrated potent cytotoxicity towards PANC-1 cells, with IC 50 of 27±0.24 μM and 35±0.51 μM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU reaches higher levels in cancer cells than in systemic circulation when administered intravenously. One 5-FU pro-drug is capecitabine, which is converted into its active form after oral administration (11,188,191,253,278,302). start of the first cycle of chemotherapy (174,175).…”
Section: Antimetabolitesmentioning
confidence: 99%